Hal-hal Yang Ada Hubungan dengan Kejadian Stunting Pada Balita Di Beberapa Daerah Di Indonesia Periode Tahun 2011 Sampai Dengan Tahun 2021 - Kindangen, Mega Chintya Patiung; Sartika, Suriana Dwi; Palaguna, Sriwati (Fakultas Kedokteran Universitas Bosowa, 2024)
Stunting is a condition where toddlers experience impaired growth and development that caused by malnutrition and repeated infection which could limit children’s physical and cognitive capacity. This study aims to identify few possible matters that may correlated with the occurrence of child stunting in several regions in Indonesia for the period 2011 to 2021. A literature review method of eleven previous scientific research journals was an analytical method with a case control research design. The results of analyzing eleven scientific studies showed that the occurrence of child stunting in Indonesia was significantly correlated with exclusive breastfeeding, low birthweight, history of infectious diseases, mother’s educational background, and parenting.In summary, factors that played huge role in occurrence of child stunting for decade (2011-2021) in Indonesia were exclusive breastfeeding, low birthweight, history of infectious diseases, mother’s educational background and parenting.